Does it pay for US-based NGOs to go to war? Empirical evidence for Afghanistan and Iraq - Youngwan Kim; Peter Nunnenkamp (Kiel Institute for the World Economy (IfW), 2013)
Apart from altruistic reasons, NGOs may engage in developing countries under conditions of conflict and war in order to secure funding and survive in the 'market' of humanitarian relief and development assistance. Applying a difference-in-difference-in-differences approach, we analyze empirically whether the presence of US-based NGOs in Afghanistan and Iraq improved their chances of external funding. We find that NGOs being active in Afghanistan tended to benefit from easier access to official sources of funding after the US intervention, compared to NGOs staying away. Nevertheless, there is no compelling evidence that it pays for NGOs to engage where the United States intervenes militarily.
Keywords: L31; F35; F51; 330; NGOs; official funding; private donations; Afghanistan; Iraq